Pengembangan Media Pembelajaran Interaktif Game Ular Tangga Berbasis Unity 3D Pada Mata Pelajaran Kearsipan Kelas X OTKP di SMKN 4 Surabaya - Anis Inawati; Durinta Puspasari (Universitas Negeri Surabaya, 2020)
Lack of interactive learning media used by teachers in the learning process tends to make students easily bored and have difficulty in understanding the material. So the teacher is expected to be able to make interactive learning media interesting and appropriate for use in the learning process. This research aims to describe the process of developing interactive learning media for snakes and ladders game based on 3D unity in the X-class OTKP subjects in SMKN 4 Surabaya. This type of research is research and development (Research and Development). The development model used in this study is ADDIE (Analysis,Design, Development, Implementation, and Evaluation), but this developmentresearch only reaches the Analysis and Design stage only because of the limitations of researchers. The results showed that at the analysis stage to find out some problems, the researcher conducted a preliminary study at Vocational High School 4 Surabaya by conducting interviews with Filing subjects directly and conducting interviews using several questions in a questionnaire. Then the researchers conducted an analysis of the characteristics of students. and then the researchers conducted the competency and instructional analysis stages. After the analysis phase is completed, the design phase is carried out. In the design phase the researchers made the initial design of interactive learning media making game snakes and ladders based on unity 3D. at this stage the researchers designed the learning media by creating storyboards about the snakes and ladders game. Storyboard function is used as a guide for making it easier in the process of making learning media